Bilirubin Protects Transplanted Islets by Targeting Ferroptosis - Yao, Qing; Sun, Rui; Bao, Shihui; Chen, Ruijie; Kou, Longfa (Frontiers in Pharmacology, 2020)
Islet transplantation is an attractive treatment for type 1 diabetic patients. However, transplanted islets suffered from considerable cell death due to inflammatory reactions and oxidative stress. Ferroptosis is a programmed death characterized by iron-dependent lipid peroxidation, which has been implicated in the islet loss and dysfunction. Our previous studies showed that bilirubin displayed protection effect for islets by inhibiting early inflammation and oxidative stress. However, whether bilirubin protects islets by targeting ferroptosis has not yet been elucidated. Here, the isolated islet was exposed to ferroptosis-inducing agents with or without bilirubin. Islet viability, insulin secretion, and oxidative stress levels were assessed. Subsequently, the pretreated islets were transplanted into the subrenal site of streptozotocin-induced diabetic mice. Bilirubin could significantly attenuate ferroptosis in isolated islets, along with reduced oxidative stress, elevated GPX4 expression and upregulation of Nrf2/HO-1. Experimental data also confirmed that bilirubin could chelate iron. In vivo graft study demonstrated that euglycemia was achieved in diabetic mice receiving bilirubin-pretreated islets within 24 hours, while the control islets required at least 7 days. Bilirubin could improve islet viability and function through inhibiting ferroptosis, which could be of clinic interest to apply bilirubin into the islet transplantation system.